(On) the reasons for invalidity of wills in Serbian and comparative law - Vidić Jelena Đ.; Kovačević Milica S. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2025)
Abstract: In order to be legally valid, a will, as a legal act mortis causa, must fulfill certain conditions as prescribed by each specific legal system. Under Serbian law, a will can only produce legal effects if it has been executed by a testator with testamentary capacity, who freely expresses their will, and whose content is in accordance with positive legal provisions and rules of morality, while being made in one of the forms prescribed by law. The absence of any of these elements renders the will invalid. The legal order of each country evaluates the reasons for the invalidity of a will and classifies them accordingly as void or voidable wills. Voidness, as a type of civil law sanction, aims to strengthen legal certainty by protecting the public interest and the security of legal transactions. On the other hand, voidability, as a sanction of lesser legal effect, primarily impacts the private interests of the interested parties, which is why its scope is narrower. The Serbian Law on Inheritance clearly distinguishes between void and voidable wills in terms of the causes leading to their invalidity, the entitled persons who can invoke them, the time limits within they can be asserted, and the legal consequences of annulment. While generally falling within the framework of traditional reasons for the invalidity of legal acts as contained in the Law on Obligations, some of the reasons for voidness and voidability, as well as certain procedural aspects of the invalidity of wills, have been adapted to the specifics of a mortis causa legal act and inheritance law. This paper examines the manner in which the aforementioned issues are regulated in Serbian law, as well as in other contemporary legal systems such as German, Austrian, French, and Russian law, with a particular focus on the legal solutions accepted in domestic law. Based on this analysis, while consulting current legal doctrine and case law and also taking into consideration certain favorable solutions found in comparative law, the authors present appropriate proposals that could contribute to the improvement of the legal regulation concerning the reasons for the invalidity of wills in Serbian legislation de lege ferenda.